Arbitrase Ex Aequo Et Bono dan Hukum Islam - Anwar, Syamsul (UIN Sunan Kalijaga, 2017)
Abstract: This article deals with a form of alternative disputes resolution known as arbitration ex aequo et bono in its relation to Islamic law. Using an usu>li> approach, the writer brings into the fore the question whether Islamic law recognizes this legal doctrine and analyzes it in the light of Quranic verses, Prophetic traditions, Islamic legal maxims, and the opinions of Muslim classical as well as contemporary scholars. The data of the study comprise primary, secondary, and tertiary Islamic legal materials collected from the sources such as the Quran, and relevant books on Quranic exegesis, hadith lirature, fiqh and al-qawa>ʻid al-fiqhiyyah treatises. The writer come to a general conclusion that, while arbitration ex aequo et bono becomes an increasingly accepted legal doctrine in modern times, Muslim jurists see that there hardly any room for cancelling the sharia in arbitration process in favor of ex aequo et bono principle.Abstrak: Tulisan ini mengkaji salah satu bentuk alternatif penyelesaian sengketa yang dikenal dengan istilah arbitrase ex aequo et bono dalam kaitan dengan hukum Islam dengan fokus pada persoalan apakah hukum arbitrase syariah mengakui doktrin ex aequo et bono? Pendekatan yang digunakan adalah usul fikih dengan sumber kajian meliputi Al-Qur’an, kitab-kitab hadis, kitab-kitab tafsir, kitab hadis dan fikih serta sejumlah pustaka lainnya yang terkait. Penulis menyimpulkan bahwa, meskipun tahki>m ex aequo et bono telah semakin banyak diterima dalam hukum modern, para ahli hukum Islam melihat bahwa kecil peluang dimungkinkannya mengabaikan hukum Islam dalam pemberian keputusan hukum melalui arbitrase.